Trauma, intellectual and/or developmental disability, and multiple, complex needs: A scoping review of the literature. (August 2021) - Cook, Shelley; Hole, Rachelle
Highlights: There is limited research on trauma and IDD and it is not cleaning linked together. Research related to trauma and IDD is not cleanly linked together. Current approaches primarily focus on interventions at the individual level. Also needed are studies on trauma/PTSD and IDD from an organizational perspective. Abstract: Background: Trauma is a significant underlying factor in the multimorbidity of people with Intellectual and/or Development Disabilities (IDD). This relationship is further complicated by a growing recognition of a subset of multiply stigmatized individuals with an IDD and complex, intersecting health and social needs. Aim: The aim of this review was to examine what is known about trauma and people with an IDD and complex needs, as defined by Community Living British Columbia's (CLBC) Multiple, Complex Needs (MCN) framework, through a broad review of relevant literature. Method and procedures: We conducted a scoping review of the peer-reviewed (9 disability journals; 7 academic databases) and grey (2 grey literature databases) on IDD and trauma through an inclusive approach that used search criteria drawn from the defining features of CLBC's MCN Framework. Outcomes and results: Apart from there being a limited amount of research on trauma and IDD, two key findings emerged. Through differing approaches that get at issues of trauma in different ways (i.e., through adverse life events or experiences of abuse), the first finding is that the research related to trauma and IDD is not cleanly linked together. The second is the focus on treatment services or interventions and not on what's happening at the organizational or system level. Conclusion and implications: There is limited research on trauma and IDD making it even more important to unify the evidence that exists. However, the literature is not integrated across different theoretical and disciplinary perspectives. In addition, the focus of trauma-related research that is occurring is interventions at the individual versus system level. Also needed are studies that explore trauma-informed practice from an organizational or top-down perspective.